A measure of relative entropy between individual sequences with application to universal classification - Ziv, J.; Merhav, N. (IEEE transactions on information theory, 1993)
A new notion of empirical informational divergence (relative entropy) between two individual sequences is introduced. If the two sequences are independent realizations of two finite-order, finite alphabet, stationary Markov processes, the empirical relative entropy converges to the relative entropy almost surely. This empirical divergence is based on a version of the Lempel-Ziv data compression algorithm. A simple universal algorithm for classifying individual sequences into a finite number of classes, which is based on the empirical divergence, is introduced. The algorithm discriminates between the classes whenever they are distinguishable by some finite-memory classifier for almost every given training set and almost any test sequence from these classes. It is universal in the sense that it is independent of the unknown sources.< >